1996
DOI: 10.1042/bj3170747
|View full text |Cite
|
Sign up to set email alerts
|

Protection by chlorpromazine, albumin and bivalent cations against haemolysis induced by melittin, [Ala-14]melittin and whole bee venom

Abstract: The ability of the peptides melittin, [Ala-14]melittin (P14A) and whole bee venom to lyse red blood cells (RBC) and to cause shape transformation, binding, partitioning and changes in volume of the cells during haemolysis, as well as the action of the bivalent cations Zn2+ and Ca2+, chlorpromazine, albumin and plasma on the peptide-induced haemolysis of RBC in high ionic-strength solution, have been investigated. The protective effect of all inhibitors depends on whether they have been added to the media befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The lysis of cells induced by various compounds can be modulated by the presence of divalent cations the medium. This protective effect been demonstrated for many different lytic agents [17,[23][24][25]. I found that the lysis of erythrocytes induced by investigated lipids from CNSL was also inhibited in the presence of divalent cations ( Fig.…”
Section: Hemolytic and Antihemolytic Activity Of The Phenolic Lipidsmentioning
confidence: 60%
“…The lysis of cells induced by various compounds can be modulated by the presence of divalent cations the medium. This protective effect been demonstrated for many different lytic agents [17,[23][24][25]. I found that the lysis of erythrocytes induced by investigated lipids from CNSL was also inhibited in the presence of divalent cations ( Fig.…”
Section: Hemolytic and Antihemolytic Activity Of The Phenolic Lipidsmentioning
confidence: 60%
“…It has been reported that substitution of proline 14 by alanine resulted in stronger binding affinity for POPC (1-palmitoyl-2-oleoyl- sn -glycero-3-phosphocholine) membranes, less efficient leakage of fluorescent markers, different pore formation kinetics and different hemolytic mechanisms [5254]. These differences have been attributed to structural changes brought about by the mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Such a structure has not been observed for melittin. Different pore formation kinetics and hemolytic mechanisms, as well as reduced leakage and a slightly reduced hemolytic activity of P14A compared to melittin have been reported in experimental studies [49, 5254]. …”
Section: Discussionmentioning
confidence: 99%